Effectiveness of an adapted physical activity intervention for weight management in adolescents with intellectual disability: A randomized controlled trial. Issue 5 (10th January 2022) - Yu, Siyue; Gao, Yang; Wang, Aiwei; Sun, Yan; Wang, Jingjing; Kwok, Heather Hei Man; Wu, Shing; Lam, Chi Kei; Tao, Emma Dan; Jiao, Jojo Jiao; Fong, Shirley Siu Ming; Xie, Yaojie; et al.
Summary: Objective: To evaluate the effectiveness of a 9‐month school‐based adapted physical activity (APA) program for reducing weight among adolescents with intellectual disability (ID). Methods: In this randomized controlled trial, adolescents with ID, aged 12–18 years, who were overweight/or with obesity were randomly assigned into intervention and control groups. The APA intervention consisted of aerobic and resistance exercises with an overall moderate intensity and was delivered at a frequency of two sessions per week for 9 months. Changes in body mass index (BMI, primary outcome) and changes in BMIz, weight, percent body fat, waist circumference and waist‐to‐height ratio (secondary outcomes) were examined using general linear models. Results: In total 61 subjects (39 in the intervention and 22 in the control) completed the study and were included in the analyses. At 9 months, the intervention group exhibited a reduced BMI of −0.66 kg/m 2 (95% CI −1.06 to −0.25 kg/m 2, p = 0.002), while a significant increase in BMI was observed in the control group. A significant post‐intervention between‐group difference in change in BMI (−1.31 kg/m 2 [95% CI −1.99 to −0.63], p < 0.01) was found in favour of the intervention group. Similar results were also observed for all secondary outcomes. Conclusions: This study provides evidence that a 9‐month APA intervention induced clinically meaningful effects on weight loss in adolescents with ID.